Implementasi Nilai-Nilai Akhlak terhadap Dosen Kesehatan dalam Prespektif Islam di Akademi Kebidanan Yogyakarta - Mukh Nursikin (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
Islam is a divine religion that places the values of humanity or personal, interpersonal and community relations in a grand and sublime way, there is no difference from one another, justice, relevance, peace that binds all aspects of humanity. The Yogyakarta midwifery academy is an educational institution that prints professional and independent health workers, the majority of its human resources are women. Of course there are many rules and ethics that must be maintained and adhered to in their activities in providing midwifery services or in teaching and learning activities, such as language style, how to dress and so on, speaking style, how to dress, while maintaining ethics in speaking and dressing. how health lecturers can maintain morals in everyday life both in the academic and non-academic world. So that they can live calmly, respect each other and respect each other respect each other. This study uses a naturalistic approach. Resources are key people who are determined by snowball and purposive. Data are collected through observation techniques, independent interviews, interviews / dialogues and documentation. Data that has been collected is then followed by stages of description, reduction, selection, discussion, analysis and conclusions. Research Results: the implementation of healthy lecturers' ahklak values at the Yogyakarta midwifery academy in dressing the majority of hijab (Muslim fashion) Health lecturers in Muslim dress still many who have not